Different types of diabetes mellitus and risk of thyroid cancer: A meta-analysis of cohort studies - Dong, Wen-wu; Zhang, Da-Lin; Wang, Zhi-Hong; Lv, Cheng-Zhou; Zhang, Ping; Zhang, Hao (Frontiers in Endocrinology, 2022)
Objective: Sex-specific risk of thyroid cancer exists in patients with diabetes mellitus (DM). However, the risk of thyroid cancer in different types of DM is still unclear. This meta-analysis aims to clarify the real association between different types of DM with thyroid cancer risk in both sexes. Methods: We identified studies by a literature search of PubMed, EMBASE, and Cochrane Library through January 16, 2022, and by searching the reference lists of pertinent articles. The relative risks (RR) were estimated using a random-effects model. Between-study heterogeneity was assessed using the Cochran's Q and I2 statistics. Results: Compared with non-DM counterparts, the patients with DM were at 1.32-fold higher risk for thyroid cancer (95%CI 1.22-1.44) with 1.26-fold (95%CI 1.12-1.41) in males and 1.36-fold (95%CI 1.22-1.52) in females, respectively. Subgroup analysis by type of DM showed that RR of thyroid cancer in type 2 diabetes patients was 1.34 (95%CI 1.17-1.53) in the study population with 1.32 (95%CI 1.12-1.54) in males and 1.37 (95%CI 1.12-1.68) in females, respectively; RR of thyroid cancer was 1.30 (95%CI 1.17-1.43) in gestational diabetes patients; the risk of thyroid cancer in type 1 diabetes patients was 1.51-fold in females, but not males. Although there were some heterogeneities, it did not affect the above results of this study. Conclusion: This study indicates that compared with non-DM individuals, patients with any type of DM have an elevated risk of thyroid cancer. This positive association between type 2 diabetes and the risk of thyroid cancer exists in both females and males.